HUBUNGAN ISI DAN CONTEN DATA DENGAN MANFAAT NYATA PENGGUNA SIMRS DI RUMAH SAKIT JIWA ACEH TAHUN 2023 - likusman, likusman; WAHAB, BACHTIYAR (Jurnal Penelitian Kesmasy, 2025)
In the contemporary digital epoch, the deployment of Hospital Information Management Systems (SIMRS) has become paramount for the enhancement of healthcare service delivery. This investigation is predicated on discerning the correlation between the content of data, serving as the independent variable, and the tangible benefits procured from the utilization of SIMRS, the dependent variable, at the Aceh Mental Hospital during the year 2023. This study, adopting a quantitative research methodology and cross-sectional data accumulation method, garnered data via a meticulously structured questionnaire encompassing 20 items administered to the hospital personnel. The analysis of the accumulated data was performed by employing crosstab analysis and the Chi Square test, facilitated by the utilization of IBM SPSS statistical software. The findings from this research have illuminated a statistically significant correlation between the content of data and the tangible benefits derived from the utilization of SIMRS at the Aceh Mental Hospital, as indicated by a p-value of 0.036, which is less than the standard p-value of 0.05. Consequently, it can be extrapolated that the quality and categorization of data administered by SIMRS have a considerable influence on its effectiveness and benefits within the milieu of mental healthcare. Despite the significant findings, it is imperative to conduct further research employing diverse methodologies to attain.